JOB SATISFACTION AMONG ACADEMIC STAFF IN THE PUBLIC UNIVERSITIES OF THAILAND - Tarat, Sarunya; Wongsawat, Manassaphorn (PEOPLE: International Journal of Social Sciences, 2019)
This study focused on job satisfaction in various aspects: day – to – day activities, work environment, compensation, and communication. In addition, the study investigated the factors leading to potential problems such as absenteeism and turnover. All participants were from Social Sciences Cluster academic staff aged between 25 to 60 years old in the public universities situated at the lower northern region of Thailand. The survey questionnaire was applied as research instrument to collect the quantitative data. The findings revealed that the overall job satisfaction of the academic staff was high. Day – to – day activities was ranked as the highest and compensation was ranked as the lowest. Additionally, the most influential factors that led to the problem at work belonged to work overload, lack of communication and lack of professional growth and development, respectively.